2019
DOI: 10.1111/ajd.13096
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of tacrolimus as mono‐ and adjunctive therapy for vitiligo: A systematic review of randomised clinical trials

Abstract: There is currently no definitive treatment for vitiligo; various modalities include immune modulators phototherapy and skin camouflage. We investigated the efficacy and safety of topical tacrolimus either as monotherapy or combined therapy in the treatment of vitiligo. Electronic systematic search of the literature was carried out using four major databases. Randomised clinical trials (RCTs) that reported the use of topical tacrolimus in the treatment of human vitiligo have been included in a systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…While in children, the marked response was achieved only in 31.7% of patients in five studies. 7 Another recent Systematic review of RCTs, evaluated total 19 studies including 814 patients to investigate the efficacy and safety of topical tacrolimus monotherapy in treatment of vitiligo. The trials were searched to October 2018 (2005-2018, published RCTs were included) also hints that combining tacrolimus to other treatment options like steroids, phototherapy and laser may be superior to using tacrolimus alone.…”
Section: No Single Treatment Modality Has Been Shown To Have Excellent Results In Vitiligo Repigmentation By Virtue Of the Interplay Of Mmentioning
confidence: 99%
“…While in children, the marked response was achieved only in 31.7% of patients in five studies. 7 Another recent Systematic review of RCTs, evaluated total 19 studies including 814 patients to investigate the efficacy and safety of topical tacrolimus monotherapy in treatment of vitiligo. The trials were searched to October 2018 (2005-2018, published RCTs were included) also hints that combining tacrolimus to other treatment options like steroids, phototherapy and laser may be superior to using tacrolimus alone.…”
Section: No Single Treatment Modality Has Been Shown To Have Excellent Results In Vitiligo Repigmentation By Virtue Of the Interplay Of Mmentioning
confidence: 99%
“…Response rates were seen in one-fourth of patients with better response to vitiliginous lesions on the head and neck [11]. Further, three recent systemic reviews showed topical tacrolimus and NB-UVB combination to be superior to NB-UVB alone [12][13][14]. Another meta-analysis demonstrated no significant difference between NB-UVB monotherapy versus combination NB-UVB with calcineurin inhibitors [15].…”
Section: Narrowband Ultraviolet B Combination Therapy For Vitiligomentioning
confidence: 99%
“…tacrolimus) was discouraged in the past, because of concerns over a possible increased risk of skin cancer, a number of studies assessing this combination of treatment have been published over the last few years. A systematic review by Arora et al 85 identified three studies comparing a combination of NB-UVB and tacrolimus with NB-UVB monotherapy. Meta-analysis of two of these studies showed combination treatment to be more effective than NB-UVB monotherapy in achieving > 75% repigmentation, although only just (risk ratio 1.34, 95% CI 1.05 to 1.71).…”
Section: Relevance To the Wider Literaturementioning
confidence: 99%